FORMATION OF COPPER OXIDE (CU2O) CRYSTALS ON THE SURFACE OF NATURAL FIBROUS FABRICS AND STUDY OF THEIR PHYSICAL AND MECHANICAL PROPERTIES - Parpiev Khabibulla; Chunxing Zhou; Juramirza Abdiramatovich Kayumov; Zokirjon Erkinov; Adkhamjon Gafurov; Muzaffarkhon Izatillaev (Web of Journals Publishing, 2025)
Structural color-forming materials are expected to replace pigments and dyes as a new type of color materials with good light fastness and bright color. In this study, copper oxide (Cu2O) microspheres of different sizes were synthesized by a two-step spin-coating method, and the microspheres were firmly attached to fabrics using a polyvinyl alcohol (PVA) binder. Two different types of fabrics (cotton, silk) were evaluated to study their physical properties and color fastness. As a result, the tensile strength and tearing strength of Cu2O structural fabrics slightly decreased, while the tearing strength of silk fiber fabrics increased, except for cotton fiber fabrics. Meanwhile, all structurally colored fabrics showed excellent color fastness to cutting, abrasion, and washing. This study provides experimental data for developing the feasibility of using structural colors in various natural fabrics.
Keywords: Textile fabrics, structural color, photonic crystals, Cu2O microspheres, mechanical properties.